Life insurance company policy on insurance claims from beneficiaries based on policy discoveries outside the claim period (case study of Manulife Medan insurance company) - Arantik, Rida; Sativa, Annisa (LEGAL BRIEF, 2025)
This study examines the policies of life insurance companies regarding claims from beneficiaries who discover a policy after the claim deadline has passed. The case study was conducted at PT Asuransi Jiwa Manulife Medan. Problems arose when beneficiaries only learned of the policy several years after the insured's death, resulting in claims being filed outside the timeframe. This study used an empirical legal method with a statutory approach and direct interviews with the company. The results showed that although the policy stipulates a claim deadline of between 30 days and one year, PT Manulife still allows for review if the policy is still active and the reason for the delay is justifiable. Policies that still have cash value are still considered active, allowing claims to be processed. These results demonstrate the importance of fairness and consumer protection in life insurance. In conclusion, there needs to be a balance between legal certainty in contracts and protection of beneficiary rights, particularly in cases of late claims caused by ignorance of the policy's existence.